Auditory brain stem evoked potentials in patients with leprosy - Celik, O; Yalcin, S; Gok, U; Yavrucuoglu, E; Ozturk, A; Akyol, A (Int Journal Leprosy, 1997)
Nineteen, randomly selected male patients with lepromatous leprosy were evaluated electrophysiologically. All of these patients had long-standing disease and were treated with dapsone alone. There were statistically significant differences between the values obtained in this group of leprosy patients compared to 20 age-matched controls in auditory brain stem evoked potentials (ABEP). The findings are consistent with a pathologic process located mainly between the cochlear nucleus and the lateral lemniscus in the auditory brain stem pathways. It should be emphasized that our patients had long-standing disease which was treated with dapsone. ABEP could very well be different in leprosy patients diagnosed early and treated for relatively short periods with multidrug therapy. Brain stem evoked response audiometry may be useful for evaluating the possibility of brain stem involvement in leprosy.